First‐in‐Human Phase I Study of Merestinib, an Oral Multikinase Inhibitor, in Patients with Advanced Cancer. (4th March 2019) - He, Aiwu Ruth; Cohen, Roger B.; Denlinger, Crystal S.; Sama, Ashwin; Birnbaum, Ariel; Hwang, Jimmy; Sato, Takami; Lewis, Nancy; Mynderse, Michelle; Niland, Michele; Giles, Jennifer; Wallin, Johan; et al.
Abstract: Background: The purpose of this nonrandomized, open‐label, phase I study (NCT01285037) was to evaluate the safety and tolerability of merestinib, an oral antiproliferative and antiangiogenic kinase inhibitor, and to determine a recommended phase II dose and schedule for patients with advanced cancer. Materials and Methods: This was a multicenter, nonrandomized, open‐label, phase I study of oral merestinib consisting of six parts: dose escalation (part A), followed by a four‐cohort dose‐confirmation study (part B) and subsequently a four‐part dose expansion and combination safety testing of merestinib with standard doses of cetuximab (part C), cisplatin (part D), gemcitabine and cisplatin (part E), and ramucirumab (part F) in patients with specific types of advanced cancers. Safety, tolerability, antitumor activity, and pharmacokinetics were evaluated in all cohorts. Results: The dose escalation, confirmation, and expansion results support the dosing of merestinib at 120 mg once daily, based on acceptable exposure and safety at this dose. One complete response was observed in a patient with cholangiocarcinoma, and three patients with cholangiocarcinoma achieved a partial response. Overall, 60 (32%) of the 186 patients enrolled in the study had a best response of stable disease. Conclusion: This study demonstrates that merestinib has a tolerable safety profile and potential anticancer activity and warrants further clinical investigation. Implications for Practice: Merestinib treatment in patients with advanced cancer demonstrated an acceptable safety profile and potential antitumor activity, supporting its future development in specific disease populations as a monotherapy and/or in combination with other therapies. Abstract : Many cancers have upregulated MET expression. Merestinib, an oral kinase inhibitor with antitumor proliferative and antiangiogenic activity in MET‐amplified and MET autocrine xenograft tumor models, was initially developed to target the MET kinase. This article evaluates the safety and tolerability of merestinib in patients with advanced cancer.